Les Idrissides entre Fatimides et Omeyyades - Chafik T. Benchekroun (Revue des Mondes Musulmans et de la Méditerranée)
The confrontation between Fatimids and Umayyads in the Maghrib throughout the 10th century turned upside down the local and political configurations. The Idrisids, already divided and weakened at the rise of the Fatimids, were more torn with the agonizing indecisions of the berber tribes between Fatimids and Umayyads. Although pro-Umayyads, the Idrisids joined the Fatimids after the former Fatimid lieutenant Mūsā b. Abī l-ʻĀfiya left Fatimids for Umayyads. This article aims to shed light on the ideological and political inclinations and motivations of the different idrisid sides in this conflict between a Shiite and a Sunni caliphate.